DESIGN OF FOREST ECO-TOURISM AREA IN BUKIT SARIBU KARO REGENCY WITH APPROACH GREEN ARCHITECTURE - Asniar Asniar; Bhakti Alamsyah; Ramadhani Fitri (INFOKUM, 2022)
It’s undeniable right now that the tourism sector is a sector very reliable in growing the economy during the Covid-19 era where a country is no exception to Indonesia. To Increase the enthusiasm of the economy after pandemic an innovation is needed in carrying out the transformation of development especially in areas that can increase economic growth. One of the efforts related to this is reclamation of an area namely Forest Ecotourism in Bukit Saribu Karo Regency. Reclamation is carried out to overcome unavoidable environmental demage. The process of design Forest Ecotourism in Bukit Saribu Karo Regency Designed with a approach Green Architecture, The resulting ecotourism will pay great attention to various sector especially nature. The design of the Forest Ecotourism area in Bukit Saribu Karo Regancy to become an ecotourism are by managing aspect of life around it both nature and its inhabitatns. In its later construction, it is expected to produce environmentally friendly buildings that must maximize existing natural resources and not use excessive amounts of building materials.